Eskalasi Hukum dan Politik dalam Revisi Undang-Undang Mineral dan Batu Bara - Vico, Nanda; Ayu Anggraini, Sofi; Himawan Saputra, Arif; Caesar Premadani, Ade; Simanjuntak, Predderics Hockop; Imamah, Qurrotun; Firdaus Sam, Bambang Ahmad; Heri, Moh. (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Natural resources are one of the crucial objects in the dynamics of the life of the nation and the state, the management of this abundant natural resource is a very large responsibility of the state, the limitation of the state's ability is inversely proportional to the needs and potentials possessed by these natural resources so that the state makes natural resources as its business commodity in the utilization and management of natural resources. Business actors engaged in the utilization and management of natural resources need to compete with each other in order to obtain permits from the government and ease of investment, so that they can maximize the potential profits they have. This situation creates conditions for political lobbies so that the governing law can be adjusted to provide convenience for investors, one of which is the Mineral and Coal Law. This research will focus on examining the dynamics that occur to all stakeholders in the revision of the Mineral and Coal Law, by using a normative juridical research method using a legal and regulatory approach, so this research tries to map political strategies, political actors, and influencing factors. This research navigates to the hypothesis that the Mineral and Coal Law is a law oriented to business interests, so that environmental management and protection as a result of exploitation of natural resources is not optimal and futuristic.